(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Myocardial ischemia in type 2 diabetes mellitus may be painless keeping the coronary artery disease occult. Exercise Treadmill Test was one of the modes that have been tried to uncover occult coronary artery disease, yet its results were not assessed. Objective:To show the rate of occult coronary artery disease in asymptomatic type 2 diabetes mellitus subjects using exercise treadmill test, and to assess the exercise treadmill test-detected occult coronary artery disease by conventional coronary angiography , and to inspect the risk factors. Methods: A cross sectional study of 120 randomly enrolled asymptomatic type 2 diabetic subjects who were not labeled to have ischemic heart disease prior to the study. The body mass index, blood pressure, serum total cholesterol, serum triglycerides and glycated hemoglobin A1c were all measured in addition to rating of smoking trend. Exercise treadmill test was, then, conducted to all of the enrolled subjects followed by conventional coronary angiography to subjects whose exercise treadmill test was positive. Results:A proportion of 20.8% of asymptomatic type 2 diabetic subjects showed positive exercise treadmill test results (p